Crystal structure of ethanolammonium dioxo-(N-(2-ethanolato)- 2-oxy-3-methoxybenzaldiminato-O,N,O′)vanadate(V), (NH3CH2CH2OH)[VO2{(C6H4(OCH3)(O)CHNCCH2CH2O}] - Feng J.-N.; Zhou Y.-Z.; Zhu H.-J.; Tu S.-J. (Zeitschrift für Kristallographie - New Crystal Structures, 2006)
C12H19N2O6V, monoclinic, P121/c1 (no. 14), a = 8.986(2) Å, b = 13.168(2) Å, c = 13.243(2) Å, β = 108.677(2)°, V = 1484.6 Å3, Z = 4, Rgt(F) = 0.031, wRref(F2) = 0.083, T = 294 K.